An investigation on the population parameters of freshwater crayfish (Astacus leptodactylus Esch., 1823) in Lake Iznik (Bursa) - Aydin, Hamdi; Harlioglu, Muzaffer Mustafa; Deniz, Tomris (Tubitak Scientific & Technological Research Council Turkey, 2015)
Length-weight relationships, distribution of length and weight groups, sex ratio, and length compositions of the crayfish Astacus leptodactylus (Esch., 1823) population in Lake Iznik (Bursa), along with some reproductive-period characteristics (spawning periods, pleopod egg numbers, and egg incubation periods), were investigated between February 2010 and May 2011. For this purpose, 1897 freshwater crayfish samples (896 female, 1001 male) were collected, using fyke nets of 34-mm nominal bar length. It was observed that females carried pleopodal eggs during the second week of January, and they carried first-stage juveniles during the second week of June. Individuals within the 76-149 mm total length group had approximately 239.95 +/- 109.36 pleopod eggs; egg diameter was 2.763 +/- 0.150 mm. The mean total length of the individuals was 104.17 +/- 14.89 mm for females and 95.71 +/- 13.11 mm for males. The mean weight was 32.50 +/- 21.83 g for females and 28.82 +/- 14.12 g for males. As a result of regression analyses, the length-weight relationship was calculated as W = 3.10(-5) TL3.011 for females and W = 8.10(-6) TL3.3016 for males. These findings show that females of A. leptodactylus have isometric growth, but males of this species have positive allometric growth. This study reveals that the A. leptodactylus population of Lake Iznik demonstrates recovery in its situation.
Keywords: Lake Iznik; freshwater crayfish; Astacus leptodactylus; population characteristics; length-weight relationships; spawning characteristics